Simplify the expression.
9xy^2 – 11xy^2

9xy^2 – 11xy^2 = -2xy^2

Expert answered|Isshu|Points 508|

Question

Asked 1/10/2018 8:20:02 AM

Updated 1/10/2018 4:30:37 PM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Simplify the expression.
-3(b – 7)

Question|Asked by AustinK15

Not Answered

Updated 113 days ago|12/30/2018 10:49:09 AM

2 Answers/Comments

-3(b – 7)

= (-3)(b) + (-3)(-7)

= -3b + 21

= (-3)(b) + (-3)(-7)

= -3b + 21

Added 1/10/2018 9:45:11 AM

This answer has been confirmed as correct and helpful.

6. Solve the equation. Show your work. Check your answer.
3x – 7 = 5x + 19
**Weegy:** 3x – 7 = 5x + 19 ,
3x - 5x = 19+7,
-2x = 26,
- x=26/2, x=-13
(More)

Question|Asked by AustinK15

Expert Answered

Updated 1/10/2018 9:47:40 AM

3 Answers/Comments

3x – 7 = 5x + 19

3x - 5x = 19 + 7

-2x = 26

x = 26/-2

x = -13

3(-13) – 7 = 5(-13) + 19

-39 - 7 = -65 + 19

-46 = -46

3x - 5x = 19 + 7

-2x = 26

x = 26/-2

x = -13

3(-13) – 7 = 5(-13) + 19

-39 - 7 = -65 + 19

-46 = -46

Added 1/10/2018 9:47:11 AM

This answer has been confirmed as correct and helpful.

Please make sure to read the question carefully. The user asked to check your answer.

Added 1/10/2018 9:47:40 AM

Solve the equation. Show your work. Check your answer.
4y + 5 = – 31
**Weegy:** 4y + 5 = – 31 ,
4y= -31-5,
4y=-36,
y=(-36/4),
y=-9 (More)

Question|Asked by AustinK15

Expert Answered

Updated 1/10/2018 9:48:36 AM

1 Answer/Comment

4y + 5 = – 31

4y = -31 - 5

4y = -36

y = -36/4

y = -9

4(-9) + 5 = – 31

-36 + 5 = -31

-31 = -31

4y = -31 - 5

4y = -36

y = -36/4

y = -9

4(-9) + 5 = – 31

-36 + 5 = -31

-31 = -31

Added 1/10/2018 9:48:36 AM

29,738,107

questions answered

There are no comments.